Hybrid Solid Electrolyte

JP7641221B2Active Publication Date: 2025-03-06NEDERLANDSE ORG VOOR TOEGEPAST NATUURWETENSCHAPPELIJK ONDERZOEK TNO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021533286
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-19
Filing Date
2019-12-19
Publication Date
2025-03-06
Estimated Expiration
2039-12-19

Smart Images

  • Figure 0007641221000001
    Figure 0007641221000001
  • Figure 0007641221000002
    Figure 0007641221000002
  • Figure 0007641221000003
    Figure 0007641221000003
Patent Text Reader

Abstract

The present disclosure relates to a solid electrolyte that provides an ionically conductive connection between an anode and a cathode in a battery, wherein the solid electrolyte includes an ionically conductive matrix including a polymer, a metal salt dispersed in the ionically conductive matrix, and a first ceramic material, wherein the first ceramic material infiltrates at least one of the faces of the ionically conductive matrix for connection to the anode or the cathode to form a first hybrid interfacial layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to solid polymer electrolytes for alkaline (earth) metal batteries and methods for making same. [Background technology]

[0002] In alkaline (earth) metal-based batteries, the negative electrode contains an electrochemically active metal. Due to safety concerns, e.g., flammability, current metal-ion batteries, e.g., lithium-ion batteries with liquid electrolytes, are not suitable for metal battery applications. Instead, solid electrolytes, e.g., polymer electrolytes and ceramic electrolytes, can be used. Polymer-based electrolytes can be preferred over ceramic electrolytes because the materials are easier to process. However, the use of solid polymer electrolytes at ambient conditions, e.g., room temperature, often results in poor battery performance. The poor battery performance can be attributed to high contact resistance between the polymer electrolyte and the metal electrode material. Furthermore, the bulk ionic conductivity of solid electrolytes decreases with decreasing temperature. In the case of polymer electrolytes, the polymer chains become less mobile internally as the temperature decreases. For example, high resistance incompatible interfaces can form. Better performance can be obtained by operating metal-polymer batteries at elevated temperatures. Lithium Metal Polymer (LMP®) batteries manufactured by Blue Solutions SA (a subsidiary of the Bollore Group) contain a polymer electrolyte and operate with good performance at temperatures above 60° C. In electronic devices, the electronic circuit may comprise a current collector of a type such as that in electrochemical devices. For example, the electrochemical device is a battery, for example a rechargeable Li-ion solid-state battery with a current collector of a non-planar design. In the battery discharge mode, the anode is the “negative electrode” into which a flow of positive charge flows from the cathode, which is the “positive electrode”. During charging, these functions are reversed. Regardless of the charge / discharge mode, the electrochemical relationship is characterized by a charge transfer between the negative and positive electrode materials, the negative electrode material having a work function or redox potential lower than that of the positive electrode material.

[0003] For example, known negative electrode (anode during battery discharge) materials are Li4Ti5O12 (lithium titanate spinel or LTO); LiC6 (graphite); Li4.4Si (silicon) and Li4.4Ge (germanium), and known positive electrode (cathode) materials are LiCoO2 (lithium cobalt oxide or LCO), LiCoPO4, (doped) LiMn2O4 (lithium manganese oxide spinel or LMO), LiMnPO4, LiFePO4 (LFP), LiFePO4F (LFPF) or LiCo1 / 3Ni1 / 3Mn1 / 3O2 (LCNMO).

[0004] Thin-film batteries, such as thin-film solid-state lithium-ion type thin-film batteries, can be made by various deposition techniques to produce anode, cathode, and electrode materials that are combined together to form the battery. Such techniques may typically include depositing thin films of the materials using vacuum deposition or other techniques that produce similar thin films to produce a "thin-film" battery. Thin-film batteries are often used in applications where space and weight may be preferably conserved and extremely long cycle life may be desired. When batteries containing polymer solid electrolytes are operated at high temperatures, the polymer electrolyte softens and the system becomes prone to dendrite growth. US 2018 / 026302 describes a porous polyethylene separator coated with a ceramic material to prevent dendrite growth for use in combination with a liquid electrolyte. However, the electrolyte described does not address the problem of contact resistance, and furthermore, the use of a liquid electrolyte can lead to safety issues, for example, the liquid electrolyte may ignite due to a short circuit when the battery temperature is high.

[0005] Alternatively, ionically conductive ceramic materials may be used as electrolyte materials. Such materials may form a more compatible interface with the electrode materials. However, such ceramic electrode materials typically have limited bulk ionic conductivity and are typically difficult to handle and very brittle. This makes batteries containing solid ceramic electrolytes prone to cracking and / or other forms of failure. A publication by S. Zekloll et al. in Energy & Environmental Science, 2018, 11, pages 185-201 describes a microporous 3D printed ionically conductive ceramic electrolyte structure in which the pores are filled with polypropylene or epoxy polymers. The described polymer / ceramic microstructured electrolytes exhibit improved mechanical properties, but at the expense of ionic conductivity. Summary of the Invention [Problem to be solved by the invention]

[0006] Thus, there is a need to provide a solid electrolyte that has a combination of good bulk ionic conductivity, ionic transport number, and low interfacial resistance.

[0007] The present disclosure aims to provide a solid electrolyte, and a process for making the same, that alleviates one or more of the above limitations by providing a solid electrolyte comprising a polymer matrix having an infiltrated ceramic phase. [Means for solving the problem]

[0008] Some aspects of the present disclosure relate to a solid electrolyte suitable for providing an ionically conductive connection between an anode and a cathode in a battery, the solid electrolyte comprising an ionically conductive matrix including a polymer, a metal salt dispersed in the ionically conductive matrix, and a first ceramic material, the first ceramic material infiltrating at least one of the faces of the ionically conductive matrix for connection to the anode or cathode to form a first hybrid interfacial layer having enhanced ion conductivity between at least one of the anode and cathode in the battery and the ionically conductive matrix.

[0009] In some embodiments, the present disclosure relates to a solid electrolyte in which a ceramic material is infiltrated on both sides of an ionically conductive matrix for connecting to both electrodes of a battery to form first and second hybrid layers. The second hybrid layer may include a second ceramic material that is different from the first ceramic material. Alternatively, the second hybrid layer may include the same ceramic material as the first hybrid layer.

[0010] In some preferred embodiments, one or more of the faces of the ionically conductive matrix for connecting to both electrodes is provided with a first cap layer, the first cap layer comprising one or more of an ionically conductive ceramic material and a ceramic material that forms an ionically conductive material from a reaction with a negative electrode material.

[0011] Some aspects of the present disclosure further relate to a process for making the solid electrolyte of the present disclosure and products obtainable by the process. The process includes providing an ion-conducting matrix including a polymer and a dispersed metal salt; and exposing a first surface of the ion-conducting matrix to a gas-phase ceramic precursor material. The gas-phase ceramic precursor material infiltrates the ion-conducting matrix and reacts with a co-reactant to form a hybrid layer. The infiltration can lead to the dispersion of ceramic (nano)particles in the polymer matrix, which can help improve ion conductivity through the polymer matrix.

[0012] The co-reactant includes one or more selected from the group consisting of water, hydrogen sulfide, and an oxidizing plasma. In some embodiments, the co-reactant may be provided to the ion-conducting matrix 10m from a gas phase. Alternatively or in addition, when the co-reactant is water, the co-reactant may be present within the ion-conducting matrix. For example, a suitable amount of water may be introduced into the ion-conducting matrix in the step of forming the ion-conducting matrix. In some preferred embodiments, the process includes providing a ceramic cap layer. [Brief description of the drawings]

[0013] These and other features, aspects, and advantages of the presently disclosed devices, systems, and methods will become better understood from the following description, appended claims, and accompanying drawings. [Figure 1A] FIG. 1A shows a battery stack that includes a solid electrolyte that is prone to dendrite formation. [Figure 1B] FIG. 1B shows a battery stack including a solid electrolyte that includes a first hybrid layer. [Figure 2A] 2A-D show four exemplary embodiments of a solid electrolyte that includes a hybrid layer and / or a cap layer on one or more sides of the solid electrolyte for connecting to the negative or positive electrodes of a battery. [Figure 2B] 2A-D show four exemplary embodiments of a solid electrolyte that includes a hybrid layer and / or a cap layer on one or more sides of the solid electrolyte for connecting to the negative or positive electrodes of a battery. [Figure 2C] 2A-D show four exemplary embodiments of a solid electrolyte that includes a hybrid layer and / or a cap layer on one or more sides of the solid electrolyte for connecting to the negative or positive electrodes of a battery. [Figure 2D]2A-D show four exemplary embodiments of a solid electrolyte that includes a hybrid layer and / or a cap layer on one or more sides of the solid electrolyte for connecting to the negative or positive electrodes of a battery. [Figure 3A] FIG. 3A shows a multi-layer solid electrolyte formed by stacking solid electrolyte layers. [Figure 3B] 3B-C show exemplary two-dimensional and three-dimensional batteries that include a solid electrolyte. [Figure 3C] 3B-C show exemplary two-dimensional and three-dimensional batteries that include a solid electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The terms used to describe specific embodiments are not intended to be limiting of the invention. As used in this disclosure, the singular forms "a," "an," and "the" are intended to include the plural forms unless the context clearly indicates otherwise. The term "and / or" includes any and all combinations of one or more of the associated listed items. It will be understood that the terms "comprise" and / or "comprising" specify the presence of a referenced feature but do not exclude the presence or addition of one or more other features. Furthermore, when a particular step of a method is described as following another step, it will be understood that the step may immediately follow the other step, or one or more intermediate steps may be performed prior to performing the particular step, unless otherwise noted. Similarly, when a connection between structures or components is described, it will be understood that the connection may be direct or through an intermediate structure or component, unless otherwise noted.

[0015] The present invention will now be described more fully with reference to the accompanying drawings, in which embodiments of the invention are shown. In the drawings, absolute and relative sizes of systems, components, layers, and regions have been exaggerated for clarity. Embodiments may be described with reference to schematic and / or cross-sectional illustrations of possible idealized embodiments and intermediate structures of the invention. Like numbers refer to like elements throughout the specification and drawings. Relative terms and their derivatives should be construed to refer to orientations in the description or shown in the drawings being discussed. These relative terms are for convenience of description only and do not require that the system be manufactured or operated in a particular orientation, unless specifically noted.

[0016] FIG. 1A shows a schematic cross-sectional view of a comparative battery stack 100. The depicted comparative battery stack includes a solid bottom current collector 6, a solid negative electrode layer 2 (anode), a solid electrolyte layer 1 consisting of a mixture of metal salt and ion-conducting polymer, a solid positive electrode layer 3 (cathode), and a solid top current collector 5. The solid electrolyte layer acts as an ion-conducting layer, facilitating the transport of ions from the negative electrode to the positive electrode during the discharge cycle of the battery, and in the opposite direction during the charge cycle of the battery. Typically, the negative electrode includes lithium metal, and the solid electrolyte includes a polymer matrix suitable for the conduction of lithium ions. FIG. 1A further shows a typical dendrite formation problem that may occur in such a battery when it is operated, for example, at elevated temperatures, for example, above 60° C.

[0017] Without wishing to be bound by theory, it is believed that during the charging cycle, lithium ions are transported through the solid electrolyte layer and reduced to an electrochemically active state at the interface with the negative electrode. However, instead of forming a uniform electrode layer, dendrites D, e.g., sharp needles or spikes, may form from the electrode material protruding outward into the solid electrolyte layer. Such dendrites may grow until they eventually penetrate and break through the solid electrolyte layer and reach the positive electrode material where they cause a dangerous short circuit SC. It is believed that many factors play an important role in this process. These factors include the thickness of the electrolyte layer, the hardness of the electrolyte layer, and the electric field distribution during charging, as well as the operating conditions such as the charging rate, temperature, and potential. A non-uniform electric field distribution may lead to non-uniform and localized electrode material deposition, which may further lead to a non-uniform electric field distribution and exacerbate the dendrite formation. A soft and / or thin solid electrolyte layer may further increase the risk of dendrite formation.

[0018] FIG. 1B shows a schematic cross-section of a battery 101 including a solid electrolyte 10 according to one or more embodiments of the present invention. The battery consists of a stack of layers including an anode 2 and a cathode 3 separated from each other by a solid electrolyte 10. The top and bottom current collectors are not shown. According to an embodiment of the present invention, the solid electrolyte 10 includes an ion-conducting matrix 10m. In the illustrated embodiment, the solid electrolyte 10 includes a hybrid layer 10h and a cap layer 10c on the side that connects to the anode. The thickness z of the hybrid layer 10h is shown. The thickness z of the hybrid layer is preferably in the range of 10 nm to 50 μm, more preferably in the range of 50 nm to 20 μm, and most preferably in the range of 100 nm to 10 μm, e.g. 250 nm or 1 μm. Alternatively or additionally, the solid electrolyte may be present throughout the majority of the thickness of the solid electrolyte layer.

[0019] According to a first embodiment, the disclosed solid electrolyte 10 comprises an ionically conductive matrix 10m. The disclosed solid electrolyte 10 is suitable for providing an ionically conductive connection between a positive electrode and a negative electrode of a battery, such as a rechargeable battery.

[0020] The negative electrode (anode) of the battery may comprise one or more metals from the group consisting of Li, Na, K, Mg, Ca, and Al, silicon and tin, graphite. Alternatively or in addition, the negative electrode may comprise a conversion-type material, such as the corresponding metal oxide MO or a mixture thereof. The positive electrode (cathode) may comprise an insertion or conversion-based material. Suitable materials may be selected, for example, from the group consisting of metal oxides, silicon, graphitic materials, sulfur, phosphoric acid, oxygen, and air. For Li-ion batteries, for example, LiCoO2, MnO2, LiMn2O4, LiNiO2, Li x Mn y Ni z O2, LiNi 1-x Co x O2, LiNi x Co y Al z O2, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni x Mn y Co 1-x-y )O2, Li(Li x Mn y Ni z Co 1-x-y-z )O2, LiFePO4, Li2FePO4F, V2O5, V2O5-TeO2, WO3-V2O5, TiS x O y , Metal oxide MO x , Metal Fluoride MF x , metal chloride MCl x, metal sulfides MSx, or Li-VO. For other ion insertion type batteries, the positive electrode layer may include materials similar to those described above for Li-ion batteries, but with Li substituted with the other ion. For example, for a Na-ion battery, the first electrode layer 12 may include, for example, NaMn2O4; for a Mg-ion battery, the first electrode layer may include, for example, MgMn2O4; for an Al-ion battery, the first electrode layer may include, for example, AlMn2O4. x V2O3, although the present disclosure is not limited thereto.

[0021] According to a further embodiment, the ion-conducting matrix comprises a polymer P and a metal salt S. Preferably, the metal salt S is dispersed in the ion-conducting matrix 10m. The ion-conducting matrix 10m forms an ion-conducting medium. From FIG. 1B it is clear that the medium may be a continuous monolayer. For example, the ion-conducting matrix 10m forms a homogenous layer of material. Alternatively or additionally, the ion-conducting matrix 10m may comprise nanopores. Even if the medium is a dense material, small voids may be present, for example in the form of interstitial spaces. Such voids may be present, for example, between adjacent polymer chains contained in the medium. Alternatively or additionally, further voids may be present in the form of (nano)pores. In some embodiments, the ion-conducting matrix 10m may comprise a gelling polymer.

[0022] The ion-conducting matrix 10m typically comprises a polyether-type polymer. Such a polymer may be selected from the group consisting of, but is not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), polybutylene oxide, and / or blends thereof and / or derivatives thereof, such as block copolymers. The ion-conducting matrix 10m further comprises a metal salt, preferably the metal salt comprises a weakly coordinating anion, such as, but not limited to, perchlorate (ClO4), bis(trifluoromethane)sulfonimide (TFSI), bis(fluorosulfonyl)imide (FSI), and fluorophosphate (PF6). Alternatively or in addition, the ion-conducting matrix 10m may comprise a gel-based electrolyte, such as a gelled mixture of a polymer with a liquid electrolyte or other additives (such as succinonitrile and / or ionic liquids).

[0023] Preferably, the metal salt S comprises a metal ion corresponding to a metal contained in the negative electrode of a battery for which the solid electrolyte 10 is suitable. For example, in the case of a battery stack in which the negative electrode comprises metallic lithium, the metal salt S comprises lithium ions.

[0024] According to a further aspect, the ion-conducting matrix 10m comprises a first ceramic material C1, which is arranged on the ion-conducting matrix 10m such that at least one of the faces of the ion-conducting matrix 10m intended for connection to a negative or positive electrode is permeated with the first ceramic material C1. In some preferred embodiments, the ion-conducting matrix 10m has a thickness of less than 100 μm, preferably less than 25 μm, for example in the range of 25 μm to 5 μm or in the range of 10 μm to 1 μm.

[0025] By infiltrating the ion-conducting matrix 10m, it can be understood that the ceramic material infiltrates the solid electrolyte 10 layer from the face towards the bulk. In some preferred embodiments, the first ceramic material C1 infiltrates the ion-conducting matrix 10m to form a first hybrid layer 10h1 extending from the first face of the solid electrolyte 10 to the bulk of the solid electrolyte. The thickness z of the first hybrid layer is preferably at least 1% of the thickness of the ion-conducting matrix 10m. If desired, the first hybrid layer may be thicker, for example 5%, 20%, 50% or more thick, up to 100%, in which case it extends all the way to the opposite face of the ion-conducting matrix 10m.

[0026] In some preferred embodiments, the ceramic is formed in small ceramic domains. Preferably, the ceramic domains include at least one mesoscopic scale dimension. In other words, the ceramic domains in the hybrid layer preferably have at least one dimension, e.g., diameter, that has a size in the range greater than the atomic scale and smaller than the macroscopic scale. For example, the mesoscopic ceramic domains include at least one dimension in the range of 1 nm to 5 μm, preferably in the range of 5 nm to 1 μm, more preferably in the range of 10 nm to 500 nm.

[0027] The increased interfacial area between the polymer matrix and the infiltrated ceramic surface can reduce the contact resistance between the electrode and the formed solid electrolyte 10. It is believed that in all polymer solid electrolytes, the interfacial contact resistance is dominated by the interfacial area between the polymer and the electrode. By forming a hybrid material interface, the resistance can be divided into the interfacial contact resistance between the ceramic and the electrode and the interfacial resistance between the polymer matrix and the ceramic inside the hybrid layer. By increasing the area between the ceramic and the ion-conducting matrix 10m, the overall interfacial contact resistance can be reduced. The interfacial area between the ceramic and the ion-conducting matrix 10m can be improved by a) infiltrating the polymer matrix with an amount of ceramic material, b) reducing the size of the ceramic domains in the hybrid layer 10h1, and / or c) increasing the volume, e.g., thickness, of the hybrid layer to form the hybrid layer.

[0028] In a preferred embodiment, the hybrid layer comprises at least 5 volume percent of the ceramic material, preferably 10% to 90%, more preferably 20% to 80%, and even more preferably 30% to 60%. By providing a hybrid layer with a more uniform volume of ceramic material and volume of ion-conducting matrix 10m, the interfacial area between these materials may be increased. The inventors have found that the infiltration may also increase the bulk resistance of the hybrid, as the nanoparticles help to lower the Tg of the polymer matrix.

[0029] The first ceramic material C1 may comprise one or more of: a simple oxide (MO) of a metal or metalloid; a binary oxide (M1M2O); or a higher order oxide, such as a ternary oxide (M1M2M3O); a sulfide; a nitride; or a halide, such as a chloride or fluoride.

[0030] Infiltrating the ion-conducting matrix with the ceramic material may advantageously maintain the ionic conductivity of the polymer and the dispersed metal salt. Infiltrating the ion-conducting matrix with the ceramic material may create an interface with a large surface area. Preferably, the ceramic may be present in the interstices of the ion-conducting matrix 10 m. Providing a hybrid layer with a large interfacial area may improve adhesion between the ceramic material and the matrix. Providing a hybrid layer with a large interfacial area may improve ionic conductivity in the layer. For example, ions may preferentially diffuse along the interface between the ceramic domains and the matrix material.

[0031] By providing the solid electrolyte 10 with a ceramic material, the contact between the solid electrolyte 10 and other functional layers in the battery stack, such as electrode material layers, may be improved, for example, by reducing the interfacial resistance. In addition, the interfacial ceramic material may be selected to have an improved ion injection behavior into / from the electrode, which is at least better than the inherent ion injection properties of the polymer electrode. For example, by providing a suitable hybrid layer to the solid electrolyte 10 at the side for contacting the negative electrode material, such as metallic lithium, the interfacial resistance may be reduced. Alternatively or additionally, the interfacial ceramic material may be selected to have an improved ion injection behavior into / from the electrode. Batteries in which a hybrid layer is provided at the interface for connecting the negative electrode to the solid electrolyte 10 have improved performance at low temperatures, for example during charging cycles. Such improved performance may be the result of a reduced contact resistance. Furthermore, such batteries may be provided with improved charging characteristics due to improved uniformity of the electric field at the interface between the negative electrode and the solid electrolyte 10. Providing a hybrid layer with small ceramic domains may further improve the effect. Alternatively or in addition, providing the solid electrolyte 10 with a ceramic material may improve the mechanical contact between interfaces and layers in the battery stack, for example improving adhesion. The improved mechanical contact may reduce damage to the battery stack, for example damage due to delamination of the functional layers. Alternatively or in addition, providing the solid electrolyte 10 with a ceramic material may improve the mechanical properties of the solid electrolyte. This may improve the handling of the layers of the solid electrolyte 10 and reduce the risk of damage to the solid electrolyte 10, for example damage due to tearing.

[0032] In some embodiments, both sides of the ion-conducting matrix 10m for connection with the electrodes are infiltrated with ceramic materials C1, C2 to form a first hybrid layer 10h1 and a second hybrid layer 10h2. The second hybrid layer may include the same ceramic material as the first hybrid layer. Alternatively, the second hybrid layer may include a second ceramic material C2. By providing a second hybrid layer with a different ceramic material, a solid electrolyte 10 may be formed in which the adhesion and electrical properties of the side of the solid electrolyte 10 for connection with the negative electrode and the side of the solid electrolyte 10 for connection with the positive electrode can be independently adjusted. The thickness of the first hybrid layer and the second hybrid layer may be different and adjusted independently of each other, where each layer comprises at least 1% of the thickness of the ion-conducting matrix 10m. If desired, these hybrid layers may both or each individually be thicker, for example 5%, 20%, 50% or more, and may extend all the way up to 99%, for example, to the opposite hybrid layer.

[0033] In certain cases, infiltrating the polymer matrix with a ceramic material with the face facing the Li metal may improve cycling stability and reduce safety concerns.

[0034] The ceramic material may be a ceramic Li-ion electrode, e.g. LiPO(N), an oxide, e.g. TiO2, AlxOy, ZrOx, ZnOy, or a lithium salt. This improves cycling stability due to favorable interfacial kinetics as well as improved mechanical strength of the film. As an additional embodiment, a high dielectric constant ceramic material with a dielectric constant greater than 20 or even greater than 200 may be selected to homogenize Li metal growth and prevent dendritic growth by dielectric screening.

[0035] Additionally, combining two ceramic materials in a two-step process, for example combining a high dielectric constant material with a Li-ion electrolyte, may be used to combine beneficial aspects of both. Certain embodiments include: 1. Copper foil substrate coated (on both sides) with a Li metal layer less than 4μm thick 2. Then, a polymer film infiltrated with a ceramic material is laminated on the surface facing the Li metal layer, for example, but not limited to, by hot pressing; To improve adhesion and interfacial kinetics, an additional adhesion / wetting layer (e.g., gel or plastic electrolyte, or liquid electrolyte or ionic liquid) may be deposited on the Li metal / film prior to lamination.

[0036] In another or further preferred embodiment, the solid electrolyte 10 is further provided with one or more capping layers 10c. These capping layers may be provided on one or more of the faces for connection to an electrode. The one or more capping layers preferably comprise an ionically conductive ceramic material. In the case of a capping layer provided on the face for connection to a negative electrode, the capping layer may alternatively or additionally comprise a ceramic material that forms an ionically conductive material from a reaction with the negative electrode material. In some preferred embodiments, capping layers are provided on both faces of the solid electrolyte 10 for connection to an electrode, where the first capping layer and the second capping layer may comprise the same or different capping materials.

[0037] The ceramic material in the cap layer or layers may include one or more of an ion-conducting ceramic material and a ceramic material that forms an ion-conducting material from a reaction with an anode material. The ceramic material in the hybrid layer or layers may also include one or more of an ion-conducting ceramic material and a ceramic material that forms an ion-conducting material from a reaction with an anode material. Alternatively, the ceramic material in the hybrid layer or layers may include a material that is not ion-conducting. In such a case, ion conductivity in the hybrid layer may be provided by one or more of an ion-conducting matrix 10m and an interface between the ceramic and the ion-conducting matrix. Preferably, the cap layer includes a ceramic material that provides a good interface with each electrode material that the ceramic material may contact. By providing a solid electrolyte 10 with a suitable cap layer, a battery may be manufactured with improved interfacial properties between the solid electrolyte 10 and the cathode material and / or improved interfacial properties between the solid electrolyte 10 and the anode material. The improved interfacial properties may be categorized by improved adhesion properties, such as adhesive strength, and / or reduced contact resistance, and / or improved ionic conductivity, and / or improved (electro)chemical stability, and / or reduced dendrite penetration.

[0038] The interfacial stability and ionic kinetics of the cathode side of Li-ion batteries can be improved in this way. For example, polymer membranes can suffer from limited stability towards high voltage (>3.8V) cathode materials. To improve stability, oxides such as TiO2, AlxOy, ZrOx, or ceramic Li-ion electrolytes with high stability towards high voltage materials may be selected as the ceramic material infiltrating the surface facing the cathode.

[0039] A concrete example of such a stack: 1. A porous cathode layer including a cathode material (e.g., NMC, LMNO, LCO), carbon black, and a binder is disposed on a metal substrate. 2. The porous cathode layer may be filled with a catholyte that has good stability at the cathode interface, such as a liquid electrolyte, an ionic liquid, a plastic electrolyte. 3. A hybrid polymer membrane infiltrated with a ceramic material is laminated on the surface facing the cathode, which acts as a separator between the cathode and the anode, for example by hot pressing. The ceramic material improves stability at the contact point with the cathode.

[0040] Preferably, the ceramic material forming the cap layer is selected to form a cap layer with good adhesion properties, e.g., wettability, to the electrode material. In some embodiments where the solid electrolyte 10 is used with a lithium metal anode, the solid electrolyte 10 is preferably provided with a cap comprising a lithophilic material. By providing the solid electrolyte 10 with a lithophilic cap layer, a lithium battery may be produced in which a flatter lithium electrode may be formed, e.g., during the first charge cycle. In embodiments where a cap layer is provided on the surface of the solid electrolyte 10 for connection to a metal electrode, the cap preferably has a modulus higher than that of the metal anode. For example, for solid electrolytes for use in lithium metal batteries, the hardness of the cap layer is preferably greater than 4.9 GPa. By providing the solid electrolyte (10) with a cap layer having a hardness greater than that of the metal electrode, dendrite formation may be reduced.

[0041] In other or further embodiments, a further ceramic cap is provided on the first cap layer to form a stacked multi-layer solid electrolyte 10, such as a solid electrolyte (10) comprising a stack of cap layers, where the further ceramic cap material is ionically conductive or the reaction product of the metal electrode material and the further ceramic cap material is ionically conductive.

[0042] 2A-2D are schematic cross-sectional views of four embodiments of a solid electrolyte 10 incorporating one or more of the features described above. FIG. 2A illustrates an exemplary embodiment of a solid electrolyte 10 in which two opposite faces of an ion-conducting matrix 10m are provided with hybrid layers 10h1 and 10h2 having different thicknesses z1 and z2. FIG. 2B illustrates an exemplary embodiment of a solid electrolyte 10 in which two opposite faces of an ion-conducting matrix 10m are provided with hybrid layers and further provided with a ceramic cap layer 10c on one of the faces of the solid electrolyte 10. FIG. 2C illustrates an exemplary embodiment of a solid electrolyte 10 including a cap layer and a hybrid layer on a first face and a second cap layer 10c on the opposite face of the solid electrolyte 10. 2D depicts an exemplary embodiment of a solid electrolyte 10 in which the hybrid layer is infiltrated through the entire thickness of the ion-conducting matrix, and first and second cap layers 10c1, 10c2 are provided on opposite sides of the infiltrated ion-conducting matrix 10m. It is understood that the depicted exemplary embodiment should not be taken as a limiting example. The present invention further relates to solid electrolytes 10 that include different or additional combinations of ion-conducting matrix, hybrid layer, and ceramic cap layer.

[0043] In a preferred embodiment, the ion-conducting matrix 10m may have a first ceramic cap on the side for interfacing with a negative electrode material (anode) and a second ceramic material may be impregnated on the side for interfacing with a positive electrode material (cathode). In another or further preferred embodiment, the ion-conducting matrix 10m may have a first ceramic cap on the side for interfacing with a positive electrode material (cathode) and a second ceramic material impregnated on the side for interfacing with a negative electrode material (anode). In some embodiments, the solid electrolyte 10 includes cap layers on both sides of the ion-conducting matrix 10m for interfacing with both electrodes.

[0044] It will be appreciated that the hybrid layer(s) and cap layer(s) may be formed using the same ceramic material.

[0045] Advantageously, the ceramic materials included in the hybrid layer and / or the cap layer may be independently selected. By impregnating and coating the solid electrolyte 10 with different ceramic materials, the conductive and interfacial properties of the formed solid electrolyte may be independently optimized. For example, a first ceramic material may be selected for impregnating the ion-conducting matrix 10m, and a second, which may or may not be different, ceramic material may be selected for optimal mechanical properties and / or optimal contact resistance at the interface with the electrode material.

[0046] In one embodiment, such as the embodiment shown in FIG. 3A, the present disclosure further relates to a multi-layer solid electrolyte 20. The multi-layer solid electrolyte may be formed by stacking two or more solid electrolyte layers 10 according to the present invention. In the illustrated exemplary embodiment, the multi-layer solid electrolyte includes three ion-conducting matrices 10m, 11m, and 12m, three hybrid layers 10h, 11h, and 12h, and three cap layers 10c, 11c, and 12c. It will be understood that the multi-layer solid electrolyte 20 is not limited to the illustrated embodiment. Other stacks formed from two or more of any of the solid electrolytes 10 described in the present disclosure are also envisioned.

[0047] It will be further understood that aspects of the present invention also relate to a battery including a solid electrolyte 10 according to any of the preceding claims. In one embodiment, such as the embodiment shown in FIG. 3A, a battery 102 is formed with an essentially two-dimensional stacked architecture. The exemplary two-dimensional battery stack is depicted in cross-section and includes an anode layer 2 connected to a current collector 2c; a cathode layer 3 connected to a current collector 3c; and a solid electrolyte 10 according to any of the solid electrolytes 10 described in the present disclosure. Advantageously, the process for the manufacture of the solid electrolyte 10 according to the present invention may also be compatible with the manufacturing process of a three-dimensional battery. A three-dimensional battery typically includes a structured current collector consisting of a base structure including an array of conductive elements arranged at a distance from each other and extending away from the base. On top of these elements, further functional layers, such as electrodes and / or electrolytes, are provided, preferably in a conformal manner such that the three-dimensional battery includes a larger interfacial area between the functional layers and may deliver a larger current than a corresponding two-dimensional battery. Thus, in another or further embodiment, the present disclosure relates to a battery 103 further comprising a three-dimensional current collector structure, where at least one electrode material largely conforms to the three-dimensional structure. Optionally, many of the layers in the stack conform at least partially to the three-dimensional structure. FIG. 3C depicts a cross-sectional view of a three-dimensional battery comprising an anode layer 2 connected to a three-dimensionally structured current collector 2c; a cathode layer 3 connected to a current collector 3c; and a solid electrolyte 10 according to any of the solid electrolytes of the present invention. In some preferred embodiments, the battery comprises an anode comprising metallic lithium, a metal salt comprising lithium ions. Preferably, in such a battery, the solid electrolyte 10 may be provided with a ceramic coating comprising a lithium-affinity material.

[0048] Aspects of the present disclosure further relate to a process for the manufacture of a solid electrolyte. In one embodiment, the manufacturing process comprises obtaining an ion-conducting matrix 10m comprising a polymer P and a metal salt S dispersed in the ion-conducting matrix. Preferably, the ion-conducting matrix 10m may be obtained in the form of a membrane that may be provided on a carrier substrate, or the ion-conducting matrix may be provided as a free-standing membrane. The process for the manufacture of a solid electrolyte of the present disclosure further comprises providing the ion-conducting matrix 10m to a station for impregnating the layer with a ceramic material. In a preferred embodiment, the impregnation may be performed by chemical vapor infiltration. The chemical vapor infiltration comprises exposing a face of the ion-conducting matrix 10m to a vapor-phase ceramic precursor material. The vapor-phase ceramic precursor material permeates the ion-conducting matrix 10m and reacts with the co-reactant to form a hybrid layer. Optionally, the ceramic precursor material permeates the ion-conducting matrix 10m through the entire thickness of the matrix to form a hybrid layer extending through the full thickness of the ion-conducting matrix 10m. Suitable ceramic precursor materials typically include low vapor pressure metal-organic compounds. Suitable co-reactants may be selected from the group consisting of water, H2S, and oxidizing plasma. The co-reactants may be provided in the gas phase.

[0049] The ion-conducting matrix 10m may be provided on a substrate. Alternatively, the solid electrolyte 10 may be manufactured using a free standing ion-conducting matrix 10m film. If desired, the manufacturing process of the solid electrolyte 10 may be integrated into the manufacturing process of a battery including the solid electrolyte 10 according to any of the preceding claims. For example, the substrate may comprise one or more of the current collector and electrode materials, which are intermediate products during a layer-by-layer manufacturing process of, for example, a stacked battery.

[0050] In a preferred embodiment, the infiltration process is carried out using a chemical vapor deposition process, such as chemical vapor deposition (CVD), physical vapor deposition (PVD), and atomic layer deposition (ALD) or spatially separated variants thereof (sALD), or a gas phase reaction in the matrix. Alternatively or additionally, the infiltration process may be carried out using a wet chemical process. Preferably, the ceramic precursor materials and / or co-reactants are added in a time- or space-separated manner. By providing the ceramic precursor materials and / or co-reactants in a time- or space-separated manner, control over the reaction process, such as the amount of ceramic material formed and the infiltration depth, may be obtained. By using the sALD process, the fabrication of the solid electrolyte (10) may be advantageously integrated into a roll-to-roll manufacturing process.

[0051] Without wishing to be bound by theory, it is believed that one or more of the aspects (i-vi) allow for the formation of a hybrid layer: (i) exposing a face of the ion-conducting matrix 10m to a ceramic precursor material, e.g., a gas-phase ceramic precursor material, may cause the precursor material to infiltrate, e.g., penetrate, the matrix towards the interior of the matrix; (ii) the penetration into the matrix may be facilitated by a form of diffusion of the (gas-phase) precursor material into or along the pores or interstices of the ion-conducting matrix 10m; (iii) within the pores of these interstices, the ceramic precursor material may react with a co-reactant to form a ceramic material; (iv) since the ceramic is formed in the pores or interstices of the matrix, e.g., between adjacent chains of polymers contained in the matrix, the formed ceramic domains may be small, e.g., the formed ceramic domains may have mesoscale dimensions, e.g., diameters; (v) the co-reactant may also be delivered in the gas phase, in which case the co-reactant may also penetrate the ion-conducting matrix 10m; (vi) the ceramic precursor materials and the co-reactant may be delivered in a temporally and / or spatially separated manner, providing control over the amount and / or penetration depth of the multiple reactants into the ion-conducting matrix 10m.

[0052] The amount of gas-phase ceramic precursor material impregnated into the ion-conducting matrix 10m and the depth to which it impregnates the matrix may be adjusted by one or more of the exposure concentration and / or pressure, the exposure temperature, the exposure time, and the time lapse between successive exposures. For example, increasing the exposure concentration, the exposure pressure, and / or the exposure time may increase the amount of ceramic formed. Increasing the delay between successive exposures may increase the time that the precursor material can diffuse deep into the ion-conducting matrix 10m before reacting with the co-reactant, increasing the impregnation depth. An elevated exposure temperature may increase the diffusion rate, thereby increasing the impregnation depth. In some preferred embodiments, water is the intended co-reactant. Instead of or in addition to providing water to the matrix from the gas phase, the ceramic precursor material may react to form a hybrid layer with water, which may be dispersed throughout the ion-conducting matrix 10m. Advantageously, the polymer P included in the ion-conducting matrix 10m is typically a polyether-type polymer that absorbs water well. The entrapped water may be a residue from the formation or deposition process of the ion-conducting matrix 10m. If desired, the amount of water dispersed throughout the matrix may be adjusted by applying one or more of pressure and temperature gradients. In other words, controlled partial drying of the wet ion-conducting matrix 10m may provide the matrix with an appropriate amount of water. By providing the ion-conducting matrix 10m with an appropriate water profile, the penetration depth of the ceramic precursor material may be controlled. For example, by partially depleting the water from the matrix near the matrix surface, the ceramic vapors may diffuse deeper into the bulk of the matrix before reacting with the water, i.e., the thickness of the hybrid layer may be increased. By increasing the amount of water throughout the matrix, each reactive vapor may react closer to the surface, and therefore the penetration depth may be decreased, i.e., the thickness of the hybrid layer may be decreased.

[0053] 2A, it can be seen that the precursor diffusing from the surface of the ion-conducting matrix 10m toward the bulk forms a hybrid interface layer 10h1, 10h2, where the concentration of the infiltrated ceramic material, expressed as a volume concentration of ceramic per unit volume of the hybrid layer, gradually decreases from an initial value at the outer surface of the solid electrolyte to a lower value toward the ion-conducting matrix 10m. In some embodiments, the volume concentration of the ceramic material at the interface with the ion-conducting matrix may gradually decrease to 0. In other embodiments, such as those in which the ceramic precursor is provided from both ends as shown in FIG. 2D, the volume concentration in the bulk of the solid electrolyte may be higher, for example about 5% of the volume concentration at the outer interface, or, for example, more than 10% or even more than 25%. In some particular embodiments, such as those in which the precursor exposure is continued until the ion-conducting matrix is ​​uniformly saturated, the formed hybrid interface layer may have a substantially uniform volume concentration of the infiltrated ceramic material. The volume concentration of the ceramic material on the surface of the ion-conducting matrix intended to connect to the negative or positive electrode is generally higher than the volume concentration of the ceramic material in the bulk of the solid electrolyte. In some embodiments, the volume concentration of the ceramic material on the surface of the ion-conducting matrix intended to connect to the negative or positive electrode is 10% or more, for example 15% or 30%. In some embodiments, such as those in which a ceramic cap layer is formed on the hybrid interface layer (as shown in FIG. 2D), there may be no boundary between the cap layer and the hybrid layer, i.e., the hybrid layer may be understood to be gradually continuous into the cap layer. In other words, the volume concentration of the ceramic material on the surface of the ion-conducting matrix intended to connect to the negative or positive electrode may be approximately 100%.

[0054] Furthermore, as the ceramic precursor materials diffuse to progressively greater depths through the ionically conductive matrix, the ceramic domains formed may have shapes similar to the diffusion paths as the ceramic precursor materials react to form the ceramic material. For example, in a homogeneous or dense ionically conductive matrix, the diffusion paths, e.g., voids, may exist in the form of, e.g., interstitial spaces, which may exist, e.g., between adjacent polymer chains contained in the medium. Thus, the ceramic material formed may adopt an elongated shape with at least one dimension on the mesoscopic scale and another dimension along the diffusion path that is longer than the first dimension, preferably at least 5 times longer, preferably at least a factor of more, e.g., at least 10 times longer, or even at least 50 times longer. Because ions may preferentially diffuse along the interface between the ceramic domain and the matrix material, providing elongated domains or a network of interconnected ceramic materials may improve ionic conductivity in the solid electrolyte. The ceramic domains in the hybrid layer preferably have at least one dimension, e.g., a diameter, that has a size in the range of greater than the atomic scale but smaller than the macroscopic scale. For example, as explained above, the mesoscopic dimension may be in the range of 1 nm to 5 μm, preferably in the range of 5 nm to 1 μm, and more preferably in the range of 10 nm to 500 nm. The dimension in the other direction may be as long as the thickness of the hybrid interface layer, for example 10 nm to 50 μm, more preferably in the range of 50 nm to 20 μm, and most preferably in the range of 100 nm to 10 μm, such as 250 nm or 1 μm. Furthermore, in some embodiments, the ceramic domains may form an interconnected network, i.e., a connected ceramic pore network, where opposing portions are separated by an ion-conducting matrix (10 m), as opposed to a uniform or randomly distributed composite of isolated particles in a matrix.

[0055] A continuous layer may be understood to include a layer consisting of or including a continuous matrix that provides a continuous, i.e., uninterrupted, pathway through the layer from one surface (e.g., the top surface) to the opposite surface (e.g., the bottom surface). The continuous pathway, e.g., ion diffusion pathway, is preferably uninterrupted by internal interfacial layers that may exhibit additional diffusion barriers and / or reduced mechanical properties. Such additional diffusion barriers and / or reduced mechanical properties may be due, for example, to delamination that may occur at the interface. It will be understood that a continuous layer, e.g., an ion-conducting matrix, may be understood to be a composite material, e.g., a blend or copolymer, and / or to include inclusions, e.g., infiltrated ceramic domains.

[0056] In another or further preferred embodiment, the process further comprises providing one or more ceramic cap layers. The ceramic material may be formed from a reaction between a suitable ceramic precursor material and a co-reactant. Preferably, the reactant may be applied using a chemical vapor deposition process such as CVD, PVD, ALD, and sALD. Alternatively or additionally, the reactant may be applied by a wet chemical technique, including but not limited to spray coating, e.g., spray coating of nanoparticles. Advantageously, the formation of the hybrid layer and the ceramic cap layer may be performed using the same tool, e.g., using the same process. Optionally, the cap layers may be formed using different deposition methods. Optionally, the cap layers may be formed from different ceramic materials. Optionally, the formed cap layer may be provided with a further cap layer.

[0057] In some preferred embodiments of the process, one or more of the ion-conducting hybrid layer formation and the cap layer formation are also performed on the second side of the ion-conducting matrix 10m.

[0058] In other or further preferred embodiments, the process further comprises depositing an electrode material. Advantageously, the process may be integrated into a process for manufacturing a battery. Thus, following formation of the solid electrolyte 10, the process may comprise depositing a positive electrode material on the solid electrolyte 10. Alternatively, the formation of the solid electrolyte 10 may be followed by depositing a negative electrode material.

[0059] The continuous ion-conducting matrix may be connected to the negative or positive electrode by melt infusion of the hybrid polymer membrane. The single continuous ion-conducting electrolyte matrix is ​​infiltrated with ceramic material. The side with the highest volume content of ceramic is deposited, for example, on the first electrode, which may be the cathode or anode, and has a thickness of, for example, several 10s of microns to 200 μm and a porosity of 20% to 95%. The melt infusion process can then be used to infiltrate the side of the hybrid polymer membrane that is free of ceramic material or has a low concentration of ceramic material into the pores of the first electrode. By increasing the temperature close to or slightly above the melting temperature of the conductive matrix and simultaneously applying pressure, the surface facing towards the first electrode will melt and infiltrate into the pores of the matrix of the first electrode, while the surface facing away from the first electrode will have a higher Tmelt and will remain in a solid / glassy / rubbery state due to being infiltrated with more ceramic material.

[0060] The penetration depth of the ceramic electrolyte may typically be 5 μm or 10 μm or 20 μm. The second electrode may be placed directly on top or an additional electrolyte layer (solid, liquid electrolyte, with or without a separator membrane) may be used on the second electrode side.

[0061] In this example, it is possible for there to be multiple types of ceramic material on one side or on both sides, with the main difference between the two sides being the average volume concentration of the ceramic, with the lower average volume concentration of ceramic on the porous electrode side resulting in this portion being melt infused into the porous electrode.

[0062] Such a process may be repeated to obtain a staggered (cathode-anode-cathode) pattern of electrodes, which together with a single continuous conductive matrix filled together form a 3D battery stack. These electrodes may be porous or non-porous, in the latter case for example fully dense electrodes. In addition to the functionality described above (improved conductivity and stability), the ceramic materials infiltrated on the top surface, such as AlxOy, ZrOx, can protect the 3D battery stack from degradation when exposed to O, N, HO rich environments.

[0063] The porous electrode may be filled with a single continuous ion-conducting matrix, which may be present, for example, 1 μm, 5 μm, 10 μm, 20 μm, 40 μm above the cathode material. The membrane is then subjected to a deposition process to infiltrate the top surface with a ceramic material. The ceramic material or materials may be solid electrolytes such as LIPON, LAGP, or oxides such as AlxOy, TiOx, ZnOx, ZrOx, Li-salts, or combinations thereof.

Claims

1. - a continuous ion-conducting matrix (10m) comprising a polymer (P), and a metal salt (S) dispersed in said ion-conducting matrix (10m), and - a first ceramic material (C1) as well as a second ceramic material (C2) Including, said ion-conducting matrix (10m) for connecting to the negative or positive electrode is infiltrated on both sides with ceramic materials (C1, C2) to form a first hybrid interface layer (10h1) and a second hybrid interface layer (10h2) having improved ionic conductivity between at least one of the negative and positive electrodes in the battery and said ion-conducting matrix, said second hybrid interface layer may comprise a second ceramic material (C2) or may comprise the same ceramic material as said first hybrid interface layer; The hybrid interface layer (10h1) has a thickness of 100 nm to 10 μm; A solid electrolyte (10) for providing an ionically conductive connection between the negative and positive electrodes in a battery.

2. 2. The solid electrolyte (10) of claim 1, wherein a first cap layer (10c) is provided on one or more of the faces of the ion-conducting matrix (10m) for connecting to the negative or positive electrode, the first cap layer (10c) comprising one or more of the following: - an ionically conductive ceramic material, and a ceramic material which forms an ionically conductive material from a reaction between said ceramic material and the negative electrode material.

3. 3. The solid electrolyte (10) of claim 2, wherein the ion-conducting matrix (10m) is provided with a first ceramic cap layer (10c1) on a surface intended to interface with a negative electrode material and is impregnated with a second ceramic material on a surface intended to interface with a positive electrode material.

4. 3. The solid electrolyte (10) of claim 2, wherein the ion-conducting matrix (10m) is provided with a first ceramic cap layer (10c1) on a surface intended to interface with a positive electrode material and is impregnated with a second ceramic material on a surface intended to interface with a negative electrode material.

5. - a continuous ion-conducting matrix (10m) comprising a polymer (P), and a metal salt (S) dispersed in said ion-conducting matrix (10m), and - a first ceramic material (C1) Including, At least one of the faces of the ion-conducting matrix (10m) intended for connection to the negative or positive electrode is infiltrated with the first ceramic material (C1) to form a first hybrid interface layer (10h1) having improved ionic conductivity between the ion-conducting matrix and at least one of the negative and positive electrodes in the battery; Cap layers (10c1, 10c2) are provided on both sides of the ion-conducting matrix (10m) for connecting to the negative or positive electrode, The hybrid interface layer (10h1) has a thickness of 100 nm to 10 μm; A solid electrolyte (10) for providing an ionically conductive connection between the negative and positive electrodes in a battery.

6. A multilayer solid electrolyte formed from a stack of solid electrolyte layers (10) according to any one of claims 1 to 5.

7. A battery (100) comprising the solid electrolyte (10) according to any one of claims 1 to 6, disposed between a positive electrode (3) and a negative electrode (2).

8. 8. The battery of claim 7, wherein the negative electrode comprises lithium, the metal salt comprises lithium ions, and the ceramic coating facing the negative electrode comprises a lithophilic material.

9. - providing an ion-conducting matrix (10m) comprising a polymer (P) and a dispersed metal salt (S); - feeding said ion-conducting matrix (10 m) into a station for impregnating said layer with a ceramic material; - exposing a first surface of said ion-conducting matrix (10m) to a vapor-phase ceramic precursor material using a chemical vapor impregnation method; Including, the vapor phase ceramic precursor material infiltrates the ionically conductive matrix (10 m) and reacts with a co-reactant to form a hybrid interfacial layer having a thickness of 100 nm to 10 μm, the hybrid interfacial layer forming an interfacial layer having improved ionic conductivity between at least one of a negative electrode and a positive electrode in a battery and the ionically conductive matrix in a battery; A process for producing a solid electrolyte (10) according to any one of claims 1 to 5.

10. the chemical vapor impregnation method is selected from one or more of chemical vapor deposition (CVD), atomic layer deposition (ALD), and spatially separated ALD (sALD); wherein the impregnation depth of the gas-phase ceramic precursor material can be adjusted by one or more of the exposure concentration and / or pressure, the exposure temperature, the exposure time, and the delay time between successive exposures; 10. The process of claim 9.

11. 11. The process of claim 9 or claim 10, including providing a ceramic cap layer.

12. The process according to any one of claims 9 to 11, wherein one or more of the ion-conducting hybrid interface layer forming step and the capping layer forming step are also performed on a second face of the ion-conducting matrix (10m).

13. The process of any one of claims 9 to 12, further comprising depositing a positive electrode material and a negative electrode material.

Citation Information

Patent Citations

  • Compound coating lipo3

    JP2000348711A

  • Multilayer materials based on active lithium, methods of preparation, and applications in electrochemical generators

    JP2009544121A

  • All-solid-state lithium-sulfur electrochemical cell and method for producing the same

    JP2016524803A

  • Multilayered composite electrolyte for secondary batteries

    JP2019510349A